Nectin-4 significance in malignant neoplasms of the female reproductive system: a review of current data - Romanov, E. G.; Kokurina, K. A.; Fedotova, A. A.; Massolu, Zh.E.A.K.; Andreeva, A. I.; Khristoforova, T. S.; Ivanova, R. A.; Tarasova, K. V.; Ivanov, M. A.; Klyukina, A. E.; Sharafan, M. A.; Medvedko, E. V.; et al. (Акушерство, гинекология и репродукция, 2025)
Introduction . Nectin-4, a cell adhesion molecule of the immunoglobulin superfamily (IgSF), has been extensively studied in oncological diseases. Nectin-4 is involved in the formation of intercellular connections and promotes tumor cell proliferation, migration and chemoresistance. Upregulated nectin-4 expression has been detected in various malignant neoplasms, including tumors of the female reproductive system – ovarian, endometrial, cervical cancer, as well as rare tumors of the vulva, vagina and fallopian tubes. Aim : to summarize current data on nectin-4 role in the pathogenesis, diagnostics, prognosis and therapy of malignant tumors of the female reproductive system, and to assess the prospects for its clinical use in personalized medicine. Materials and Methods . A search for relevant publications was conducted in the PubMed/MEDLINE, Scopus, Web of Science, Embase and eLibrary.ru databases beginning from January 2000 to December 2024. The inclusion criteria covered original and review articles devoted to nectin-4 in gynecological oncology. Key words in Russian and English, Boolean operators, and filtering by full-text, subject matter, and quality of research were used. From the 3955 identified publications, 65 were included in the review. Results . Nectin-4 expression is associated with enhanced tumor cell proliferation, migration, and chemoresistance, whereas its involvement in generating tight intercellular junctions promotes the development of chemoresistant spheroids. In ovarian cancer, upregulated levels of nectin-4 messenger RNA (mRNA) and serum protein demonstrated high diagnostic and prognostic significance, especially in combination with traditional markers such as cancer antigen 125 (CA-125). In endometrial cancer, nectin-4 expression correlates with a deficiency of the mismatch repair system ( MMR genes) MSH2/MSH6 genes and lowered progression-free survival. In cervical carcinoma, nectin-4 is related to drug resistance, thereby positioning it as a promising target for novel treatment strategies. The latter using nanoquinacrine and antibody-drug conjugates (ADCs) such as 9MW2821 and ADRX-0706, are currently undergoing clinical trials. Additionally, nectin-4 has shown relevance in non-malignant reproductive disorders such as endometriosis and preeclampsia. Conclusion . Nectin-4 demonstrates high clinical significance as a diagnostic and prognostic marker in gynecological malignancies. Its expression is associated with aggressive disease progression and drug resistance, especially in ovarian, endometrial and cervical cancers. Clinical trials with nectin-4-targeted drugs, including ADCs, are underway. Thus, nectin-4 represents a promising target for the development of personalized diagnostic and therapeutic strategies in gynecological oncology.